Practical output synchronization for asynchronously switched multi-agent systems with adaption to fast-switching perturbations. (June 2020) - Xue, Mengqi; Tang, Yang; Ren, Wei; Qian, Feng
Abstract: The asynchronously switched multi-agent systems comprising switched agents of different dynamics and switching signals are considered under arbitrarily switching communication topologies. The practical output synchronization problem is studied for such a kind of systems due to the heterogeneity brought by both the dynamics and the switchings of agents. A switching-dependent controller with an embedded virtual reference system is proposed for each agent. The original problem is then converted into tracking problems between each agent and its reference system. The analysis of resultant tracking error systems involves the analysis of switched systems with bounded but non-attenuating state impulses. By satisfying sufficient conditions featuring the average dwell time (ADT) and the newly proposed piecewise ADT, the practical output synchronization can be achieved and the ultimate bound of the output errors can also be obtained for the considered systems. Furthermore, a realistic case where the agent switching signals undergo adverse fast-switching perturbations is studied. The perturbations may potentially invalidate the "slow-switching" based method. A regulation strategy is thus developed for each agent to render it adaption to such adversity. A payload transport task is taken as the practical example to illustrate the effectiveness of the proposed method and the adaption strategy.